Fodder banks: Supplementation to natural grazing - Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1984)
Lists seven steps involved in the establishment of a fodder bank package based on experimental results and literature. Presents data on intial productivity of stylosanthes fodder banks under researcher-managed and farmes-excuted trials using the seven steps, and the effect of land preparation and seed dressing on stand count/m2 of stylo cook 6 weeks after planting. Discusses the utilisation for supplementary grazing and the regeneration of fodder banks.